2017
DOI: 10.1080/1547691x.2017.1394933
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol attenuates impairments associated with lipopolysaccharide-induced acute respiratory distress syndrome (ARDS) in rats

Abstract: Celastrol, a constituent from a traditional Chinese medicinal herb belonging to the family Celastraceae, has been shown to impart anti-inflammatory properties, in part, by inhibiting NF-κB activity and related induction of pro-inflammatory cytokine formation/release. The present study investigated the effects of celastrol in an animal model of acute respiratory distress syndrome (ARDS) induced by intratracheal administration of lipopolysaccharides (LPSs). Celastrol pre-treatment groups received celastrol by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…In the study reported by Shi et al (2018), this compound improved chronic obstructive pulmonary disease by decreasing interleukin-8 (IL-8), TNF-α, and monocyte chemoattractant protein-1 (MCP1) levels, as well as by increasing enzymatic antioxidant defenses in mice [ 54 ]. These results are in good accordance with those previously reported by Wei and Wang (2017), who observed that celastrol reduced these pro-inflammatory cytokines and NF-kB activation in rats, showing lipopolysaccharide (LPS)-induced acute respiratory distress syndrome [ 55 ]. More recently, Iwata-Yoshikawa et al (2019) showed that NF-kB pathway was regulated by TMPRSS2 protein in the airway of a TMPRSS2 knockout murine model, after coronavirus infection [ 56 ].…”
Section: The Role Of Specific Bioactive Compounds Present In the Dsupporting
confidence: 93%
“…In the study reported by Shi et al (2018), this compound improved chronic obstructive pulmonary disease by decreasing interleukin-8 (IL-8), TNF-α, and monocyte chemoattractant protein-1 (MCP1) levels, as well as by increasing enzymatic antioxidant defenses in mice [ 54 ]. These results are in good accordance with those previously reported by Wei and Wang (2017), who observed that celastrol reduced these pro-inflammatory cytokines and NF-kB activation in rats, showing lipopolysaccharide (LPS)-induced acute respiratory distress syndrome [ 55 ]. More recently, Iwata-Yoshikawa et al (2019) showed that NF-kB pathway was regulated by TMPRSS2 protein in the airway of a TMPRSS2 knockout murine model, after coronavirus infection [ 56 ].…”
Section: The Role Of Specific Bioactive Compounds Present In the Dsupporting
confidence: 93%
“…In this case, it could reduce the levels of inflammatory cytokines such as interleukin-8 (IL-8), tumour necrosis factor-α (TNF-α), and monocyte chemoattractant protein-1 while enhancing antioxidant defences (superoxide dismutase and catalase). In rats subjected to lipopolysaccharide (LPS)-induced acute respiratory distress syndrome, celastrol could also ameliorate the inflammation-mediated injury as well as the expression levels of pro-inflammatory cytokines (TNF-α, IL-1, IL-6, and IL-8) and NF-κB (Wei & Wang, 2017). Under asthmatic condition or increased airway hyperresponsiveness, a positive outcome for orally administered celastrol both in the disease level and Th17 inhibition was observed in mice (Zeng, Lin, Zheng, Zhang, & Zhang, 2018).…”
mentioning
confidence: 99%
“…(3) In the ARDS subgroup (n=16), only penehyclidine hydrochloride (LPS) (3 mg/kg) was injected into the trachea to induce ARDS. The ARDS model was constructed as described in Lang et al [25] and Wei et al [26]. Briefly, rats were anesthetized by 2% pentobarbital (40 mg/kg) through intraperitoneal injection.…”
Section: Methodsmentioning
confidence: 99%